Revision of Mani's Figitidae types (Hymenoptera: Cynipoidea) - Forshage, Mattias; Baião, Guilherme Costa (Zootaxa, 2014)
Figitid wasps are still a poorly known group, with a major part of the species diversity undescribed, and complete uncertainty about the identity of a large part of the available names.